Epidemiology and risk factors for tinnitus after leisure noise exposure in Flemish young adults †. (1st February 2017) - Degeest, Sofie; Keppler, Hannah; Corthals, Paul; Clays, Els
Abstract: Objective : Young people regularly expose themselves to leisure noise and are at risk of acquiring tinnitus. This study examined the prevalence of leisure noise-induced tinnitus among Flemish young adults as well as the relation with sociodemographic factors, health-related variables and attitudes and beliefs towards noise. Design : A self-administered questionnaire was used to evaluate the presence of noise-induced tinnitus, the amount of leisure noise and attitudes towards noise and hearing protection. Study sample : 517 subjects between 18 and 30 years were included. Results : Temporary and chronic tinnitus occurred in 68.5% and 6.4% of the sample, respectively. Chronic tinnitus was more prevalent in male subjects and associated with more hearing-related symptoms. Furthermore, subjects with chronic tinnitus were more aware of the risks of noise and the importance of hearing protection. Finally, higher levels of leisure noise were independently associated with chronic tinnitus. Conclusions : Tinnitus is observed frequently in young adults. Results also indicate that persons with chronic tinnitus were exposed to a higher noise dose during their lives. Longitudinal studies may be useful to evaluate whether the experience of chronic tinnitus has led to behavioural changes. These findings further underpin the importance of educating youth about the risks of leisure noise exposure.